Study of Some [N-substituted] p-aminoazobenzene as Corrosion Inhibitors for Mild-Steel in 1M H2SO4 - Al-Doori, Hanan H; Shihab, Mehdi S (Al-Nahrain Journal of Science, 2018)
Azo dye derivatives were prepared as corrosion inhibitors for mild steel in 1M H2SO4 solution by weighting loss measurements as evaluation tools. It has been observed that inhibition efficiency orders are A1> A3> A2with the highest inhibiting efficiency of 82% for 10−3M. Increasing in inhibitor concentration accompanies with corrosion rate decreases, inhibition efficiencies increase and surface coverage degree increases. Semi-empirical molecular orbital calculations of prepared compounds A1, A2, and A3 as molecular models gave useful information to predict the interaction between the surface of metal and the organic molecules as corrosion inhibitors.